Navigational Practices and the Use of the Leeboard on Shallow Draft Riverine and Coastal Craft in the Yangzi and Rhine Estuaries: A Short Essay in Comparative Nautical History - Blussé, Leonard (TSEG - The Low Countries Journal of Social and Economic History, 2024)
Both in the shallow Yangtze and Rhine deltas, flat-bottomed sailing craft made use of leeboards to prevent the drift of the ship when reaching or sailing close-hauled. Without a doubt, the leeboard was invented earlier in China, but contrary to what is often suggested, the Dutch leeboard was not adopted from the Chinese example. Its invention should be considered an independent act, a case of convergence. The leeboard was introduced in the Low Countries simultaneously with the adoption of the fore-and-aft ‘jib and spritsail’ rig and the transformation from narrow to broader ship hulls during the late Middle Ages. Over time the Dutch leeboard was further refined in form: deep and narrow leeboards for seagoing fishing vessels and round and shallow leeboards for the sailing barges and pleasure craft on lakes, canals, and rivers.